The role of histone post-translational modifications in cancer and cancer immunity: functions, mechanisms and therapeutic implications - Duan, Xiaohong; Xing, Zhiyao; Qiao, Lu; Qin, Shan; Zhao, Xuejing; Gong, Yanhua; Li, Xueren (Frontiers in Immunology, 2024)
Histones play crucial roles in both promoting and repressing gene expression, primarily regulated through post-translational modifications (PTMs) at specific amino acid residues. Histone PTMs, including methylation, acetylation, ubiquitination, phosphorylation, lactylation, butyrylation, and propionylation, act as important epigenetic markers. These modifications influence not only chromatin compaction but also gene expression. Their importance extends to the treatment and prevention of various human diseases, particularly cancer, due to their involvement in key cellular processes. Abnormal histone modifications and the enzymes responsible for these alterations often serve as critical drivers in tumor cell proliferation, invasion, apoptosis, and stemness. This review introduces key histone PTMs and the enzymes responsible for these modifications, examining their impact on tumorigenesis and cancer progression. Furthermore, it explores therapeutic strategies targeting histone PTMs and offers recommendations for identifying new potential therapeutic targets.